2000
DOI: 10.1046/j.1471-4159.2000.0741627.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Anandamide Formation in the Limbic Forebrain and Reduction of Endocannabinoid Contents in the Striatum of Δ9‐Tetrahydrocannabinol‐Tolerant Rats

Abstract: Abstract:Recent studies have shown that the pharmacological tolerance observed after prolonged exposure to synthetic or plant-derived cannabinoids in adult rats is accompanied by down-regulation/desensitization of brain cannabinoid receptors. However, no evidence exists on possible changes in the contents of the endogenous ligands of cannabinoid receptors in the brain of cannabinoid-tolerant rats. The present study was designed to elucidate this possibility by measuring, by means of isotope dilution gas chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 59 publications
11
113
0
2
Order By: Relevance
“…All analytes were detectable in tissue punches of the vHip and were above the limit of quantitation for the assay (Table 1, Figure 5). The concentrations of all analytes in punched vHip tissue were similar to the range of concentrations reported in the literature for gross dissected rat hippocampal tissue [19,22,23,67]. Levels of AEA, 2-AG and PEA were all significantly higher in the vHip of fear-conditioned, formalin-treated rats which received intravHip vehicle, compared with their non-fear-conditioned counterparts (Table 1, …”
Section: Expression Of Fca Is Associated With Increases In Levels Of supporting
confidence: 81%
“…All analytes were detectable in tissue punches of the vHip and were above the limit of quantitation for the assay (Table 1, Figure 5). The concentrations of all analytes in punched vHip tissue were similar to the range of concentrations reported in the literature for gross dissected rat hippocampal tissue [19,22,23,67]. Levels of AEA, 2-AG and PEA were all significantly higher in the vHip of fear-conditioned, formalin-treated rats which received intravHip vehicle, compared with their non-fear-conditioned counterparts (Table 1, …”
Section: Expression Of Fca Is Associated With Increases In Levels Of supporting
confidence: 81%
“…It has been recently suggested that the endocannabinoid system might be a component of the brain reward circuitry and thus play a role not only in CB tolerance/dependence but also in dependence/withdrawal to other drugs of abuse (Di Marzo et al, 2000;Gonzalez et al, 2003;Centonze et al, 2004). Changes in endocannabinoid ligands and their receptors have been shown in different brain regions, with particular attention to those areas related to reinforcement processes, during dependence on powerful addictive drugs.…”
Section: Endocannabinoids In CM P Sarchielli Et Almentioning
confidence: 99%
“…Longer lasting and sufficiently frequent exposure to D 9 -THC may cause an exhaustion of arachidonic acid reserves followed by downregulation of the endocannabinoid system, weakening of its protective power, and increasing severity of psychosis. This is supported by findings of CB 1 receptor downregulation and lower levels of anandamide in CSF in schizophrenia patients frequently using cannabis (Di Marzo, 1999;Di Marzo et al, 2000;Leweke et al, 2006). Following this model, attenuated skin flushing in healthy individuals and schizophrenia patients (as reported here) may be taken as peripheral correlate of a systemic exhaustion of arachidonic acid and its derivates after continuous exposure to D 9 -THC.…”
Section: Discussionmentioning
confidence: 74%